Potential differences in receptor‐mediated G‐protein activation in postmortem human hippocampal membranes prepared from healthy controls and suicide victims - Yuji Odagaki; Masakazu Kinoshita; Miklós Palkovits; Dasiel Oscar Borroto‐Escuela; Kjell Fuxe (Wiley, 2024)
Abstract Aim Postmortem brain studies offer enormous opportunities to study molecular mechanisms associated with suicide. In the present study, conventional [35S]GTPγS binding assay and its version‐up method ([35S]GTPγS binding/immunoprecipitation assay) were applied to postmortem human hippocampal membranes prepared from suicide victims and control subjects. Methods By using conventional [35S]GTPγS binding assay, functional activations of Gi/o proteins coupled with multiple GPCRs (5‐HT1A receptor, α2A‐adrenoceptor, M2/M4 mAChRs, adenosine A1 receptor, histamine H3 receptor, group II mGlu, GABAB receptor, μ‐opioid receptor, δ‐opioid receptor, and NOP receptor) were detected by using 15 different agonists. Furthermore, 5‐HT2A receptor‐ and M1 mAChR‐mediated Gαq/11 activation and adenosine A1 receptor‐mediated Gαi‐3 activation were detectable by means of [35S]GTPγS binding/immunoprecipitation assay. Results No significant differences in pharmacological parameters of all concentration‐response curves investigated were found between suicide victims and control subjects. Significant correlations were obtained for the maximal percent increases between some distinct signaling pathways. Conclusion Although only preliminary and auxiliary results were obtained as to the potential differences between suicide victims and control subjects because of the limited number of subjects as well as unmatched age and postmortem delay, adenosine A1 receptor‐mediated Gαi/o activation and 5‐HT2A receptor‐mediated Gαq/11 activation appear worth focusing on in the future investigations. This study also indicates the possibility that some distinct signaling pathways are interrelated with each other, for example, functional activations of Gi/o proteins coupled to M2/M4 mAChR and 5‐HT1A receptor, NOP receptor, and GABAB receptor, and NOP receptor and δ‐opioid receptor.